2004
DOI: 10.1002/j.1556-6978.2004.tb01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Helping Students Help Themselves: Strategies for Successful Mentoring Relationships

Abstract: Mentoring has long been heralded as a method of training and socializing the next generation of professional counselors and counselor educators. Yet, there appears to be a disparity between the promotion and the practice of mentoring in counselor education. The authors attempted to reconcile this disparity by suggesting a set of strategies that mentors and apprentices may use as they establish and maintain successful mentoring relationships. Implications for counselors and counselor educators are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…What helped me in the research meetings was the combination of various factors: the collaborative and cooperative environment, the challenging discussions, the stories that were told, the visualizations, the affirmations and support of the faculty leader and students, the positive energy, and the effective facilitation of the meetings by the faculty leader. My experiences and previous studies (Black, Suarez, & Medina, 2004) suggest that faculty advisers and leaders challenge, coach, and support their protégés to improve skills, engage in personal growth activities, or develop their personal awareness.…”
Section: The Research Team Meetingsmentioning
confidence: 79%
“…What helped me in the research meetings was the combination of various factors: the collaborative and cooperative environment, the challenging discussions, the stories that were told, the visualizations, the affirmations and support of the faculty leader and students, the positive energy, and the effective facilitation of the meetings by the faculty leader. My experiences and previous studies (Black, Suarez, & Medina, 2004) suggest that faculty advisers and leaders challenge, coach, and support their protégés to improve skills, engage in personal growth activities, or develop their personal awareness.…”
Section: The Research Team Meetingsmentioning
confidence: 79%
“…In counseling programs, mentorship is seen as a relationship between a mentor and a protégé who are at different stages in their careers and who respect and support one another (Schwiebert, 2000). Mentoring relationships serve as a support for socialization and development of counselors (Black, Suarez, & Medina, 2004) and helps them strengthen their professional identity (Murdock, Stipanovic, & Lucas, 2013). Additionally, Clark, Harden, and Johnson (2000) found that clinical psychology students who had mentors tended to experience increased satisfaction with their program experience than did their non-mentored peers, suggesting similar implications for counseling students and further strengthening the argument for mentorship.…”
Section: Implications For Counselor Education and Supervisionmentioning
confidence: 98%
“…Mentoring promotes successful completion of doctoral work including the dissertation (Black, Suarez, & Medina, 2004). It is a developmental partnership through which knowledge, skills, and perspectives are shared to support personal and professional growth (Black et al, 2004;Buck, Mast, Latta, & Kaftan, 2009;Ku, Lahman, Yeh, & Cheng, 2008).…”
Section: Mentoringmentioning
confidence: 99%
“…It is a developmental partnership through which knowledge, skills, and perspectives are shared to support personal and professional growth (Black et al, 2004;Buck, Mast, Latta, & Kaftan, 2009;Ku, Lahman, Yeh, & Cheng, 2008). Mentees often seek various types of support from their mentors involving personal accountability, support, friendship, promotion of personal growth, and constructive feedback about student progress (Black et al, 2004).…”
Section: Mentoringmentioning
confidence: 99%